A construção da identidade de alunos de língua inglesa: suas representações a respeito do idioma e de sua aprendizagem - Alexandroni, Daniele (2007)
This dissertation aims at investigating the representations of a group of students from a language school towards the English language and its learning process. It discusses the continuing process of identity construction through the analysis of these representations. The theoretical framework of this research is based on a socio-historical perspective of development as discussed by Vygotsky (1934) and it is also supported by Bakhtin s (1929) dialogical comprehension of language. In order to contribute to a better understanding of the issues involved in the construction of identities, this study is also based on Hall (2000), Rajagopalan (1998) and Moita Lopes (2002), amongst others. As for the discussion on the topic of representations, this research is also based on Marková (2003), Moscovici (2003) and Freire and Lessa (2003), amongst others. The data were analysed according to the concept of thematic content, proposed by Bronckart (1999), based on the lexical choices made by the participants. This study was carried out on a language school in the city of Santo André throughout two years. The research followed a critical and interpretative line of inquiry realized through a case study. The representations of these students towards the language and its study were collected and the analysis revealed how their identities are formed. Results have shown that these representations indicate a view towards the language as an opportunity provider and for career development. It has also pointed that the language is seen as a mean of gaining knowledge and providing cultural awareness